A trainer's guide for participatory learning and action - Pretty, Jules; Guijt, Irene (2002)

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (Institute of Development Studies, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.

How Does Participatory Action Research Generate Innovation? Findings from a Rapid Realist Review - Snijder, Mieke; Apgar, J. Marina (Institute of Development Studies, 2021)
This Emerging Evidence Report shares evidence of how, for whom, and under what circumstances, Participatory Action Research (PAR) leads to innovative actions. A rapid realist review was undertaken to develop programme theories that explain how PAR generates innovation. The methodology included peer-reviewed and grey literature and moments of engagement with programme staff, such that their input supported the development and refinement of three resulting initial programme theories (IPTs) that we present in this report. Across all three IPTs, safe relational space, group facilitation, and the abilities of facilitators, are essential context and intervention components through which PAR can generate innovation. Implications from the three IPTs for evaluation design of the CLARISSA programme are identified and discussed. The report finishes with opportunities for the CLARISSA programme to start building an evidence base of how PAR works as an intervention modality, such as evidencing group-level conscientisation, the influence of intersecting inequalities, and influence of diverse perspectives coming together in a PAR process.
Accepted: 2021-07-23T08:48:45Z

Participation for Humanitarian Innovation - Background Paper - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

Participation for Humanitarian Innovation - Toolkit - Smith, Amy; Thompson, Martha; Saida Benhayoune; Crespo Cardona, Omar (Elrha, 2023)
A resource designed to help organisations, teams and individuals manage innovation journeys responsibly and successfully. We have partnered with MIT D-Lab to develop a new resource to drive greater diversity and inclusion within project design and implementation. The Participation for Humanitarian Innovation (PfHI) toolkit sets out a robust approach to setting expectations for and monitoring the degree of participation within research and innovation projects for, with, and by people affected by crisis. The PfHI toolkit is composed of five tools: Opportunity Adviser: Identify and prioritise the desired benefits of participation while weighing the potential barriers. Participation Matrix: Agree on the precise degree of participation to target at a given project stage. Resource Navigator: Select tools and processes to address the needs of stakeholders, the project objectives and context. Quality Guidance: Ensure engagements are delivered to the highest standard. Assessment Matrix: Collectively evaluate the degree of participation achieved during an activity or project phase, learn and adapt. By applying these tools before, during and after a research and/or innovation project, implementors can ensure that stakeholders/end-users are included and participating at the highest possible degree. We encourage users of the PfHI toolkit to consider how else to integrate the tools into existing practices. For instance, the Evaluation Matrix could be used to supplement existing MEAL activities to: Establish baselines to measure changes in participation over time. Track the degree of participation/engagement of stakeholders. Regularly assess the degree of participation. Seek feedback from participants about the degree of their participation. Monitor the progress of activities related to stakeholder engagement. Our Participation for Humanitarian Innovation toolkit represents our ongoing commitment to responsible research and innovation across our portfolio of grants and for the humanitarian sector more broadly. We hope you will consider downloading and using the toolkit on your next project.

Participatory action research - Cornish, Flora; Breton, Nancy; Moreno-Tabarez, Ulises; Delgado, Jenna; Rua, Mohi; de-Graft Aikins, Ama; Hodgetts, Darrin (Nature Reviews Methods Primers, 2023)
Participatory action research (PAR) is an approach to research that prioritizes the value of experiential knowledge for tackling problems caused by unequal and harmful social systems, and for envisioning and implementing alternatives. PAR involves the participation and leadership of those people experiencing issues, who take action to produce emancipatory social change, through conducting systematic research to generate new knowledge. This Primer sets out key considerations for the design of a PAR project. The core of the Primer introduces six building blocks for PAR project design: building relationships; establishing working practices; establishing a common understanding of the issue; observing, gathering and generating materials; collaborative analysis; and planning and taking action. We discuss key challenges faced by PAR projects, namely, mismatches with institutional research infrastructure; risks of co-option; power inequalities; and the decentralizing of control. To counter such challenges, PAR researchers may build PAR-friendly networks of people and infrastructures; cultivate a critical community to hold them to account; use critical reflexivity; redistribute powers; and learn to trust the process. PAR’s societal contribution and methodological development, we argue, can best be advanced by engaging with contemporary social movements that demand the redressingl of inequities and the recognition of situated expertise.
Number: 1 Publisher: Nature Publishing Group

The collaborative exploration of alternative futures: A different approach to Theories of Change - CEDIL programme (2022)
ParEvo is a web application that enables the collaborative construction and exploration of a range of alternative futures: likely and unlikely, desirable and undesirable. These are described in the form of a branching narrative structure, developed over a series of iterations involving the interactions of a group of participants. These detailed storylines about the future contrast with optimistic, skeletal and largely singular views of the future found in diagrammatic ToCs often encountered by evaluators. This webinar will describe a recent ParEvo exercise implemented by the Centre for the Study of Existential Risk (CSER) in Cambridge. In this exercise 11 international experts explored ideas about how global risks associated with biotechnology research could be managed, and mismanaged, in the coming four years. Including how these alternative futures were evaluated by participants and the CSER facilitators. Issues to be discussed by the panel, and others, include comparisons with other representations of Theories of Change and other approaches to the exploration of alternative futures, described variously as scenario planning, futures or foresight work. Speakers: Rick Davies, Lara Mani Tom Hobson An overview of the app can be found here: https://mscinnovations.wordpress.com/ The app website is here: https://parevo.org/

The guiding logics and principles for designing emergent transdisciplinary research processes: learning experiences and reflections from a transdisciplinary urban case study in Enkanini informal settlement, South Africa - van Breda, John; Swilling, Mark (Sustainability Science, 2019)
Transdisciplinarity is not a new science per se, but a new methodology for doing science with society. A particular challenge in doing science with society is the engagement with non-academic actors to enable joint problem formulation, analysis and transformation. How this is achieved differs between contexts. The premise of this paper is that transdisciplinary research (TDR) methodologies designed for developed world contexts cannot merely be replicated and transferred to developing world contexts. Thus a new approach is needed for conducting TDR in contexts characterised by high levels of complexity, conflict and social fluidity. To that end, this paper introduces a new approach to TDR titled emergent transdisciplinary design research (ETDR). A core element of this approach is that the research process is designed as it unfolds, that is, it transforms as it emerges from and within the fluid context. The ETDR outlined in this paper emerged through a case study in the informal settlement (slum) of Enkanini in Stellenbosch, South Africa. This case study demonstrates the context from and within which the ETDR approach and identifies a set of guiding logics that can be used to guide ETDR approaches in other contexts. The study demonstrates that the new logics and guiding principles were not simply derived from the TDR literature, but rather emerged from constant interacting dynamics between theory and practice. Learning how to co-design the research process through co-producing transformative knowledge and then implementing strategic interventions to bring about incremental social change is key to theory development in ways that are informed by local contextual dynamics. There are, however, risks when undertaking such TDR processes such as under-valuing disciplinary knowledge, transferring risks onto a society, and suppressing ‘truth-to-power’.